Levels of depression in Medical Technology students - Rosas, Marcelina (2011)
Objectives: To determine the level of depression in students of Medical Technology. Design: Descriptive, cross sectional study. Setting: Professional Academic School of Medical Technology, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: Voluntary Medical Technology students. Instrument: Beck Depression Inventory (BDI) consisting in 13 items with 0-3 scale, graded 0-4 rating no depression, 5-7 mild depression, 8-15 moderate depression, over 15 severe depression. Main outcome measures: Depression and severity. Results: From 119 students, 48,7% female and 51,3% male, 38,7% had some level of depression. Among students with some level of depression 54,4% were male. Some form of depression by age was found in 45,7% 15-19 year-old students, in 52,2% 20-25 years, 2,2% over 25 years; mild depression was encountered in 39,1%, moderate depression in 32,6%, and severe depression in 28,3%. Conclusions: In 20-25 year-old students of Medical Technology 1 out of 2 showed some level of depression. In male students 56 out of 100 had some level of depression. The study suggests application of depression preventive programs and determining underlying causes.